Julien Ries: a cardinal looking for the homo religiosus - Louzao, Joseba (Razón y fe, 2018)
A year ago the Belgian anthropologist Julien Ries was surprisingly elevated from Cardinal to Cardinalate by Benedict XVI due to his long lifetime and his passionate, and at the same time scientific, commitment to teaching, to investigation and to disclosure; confirmed through his eleven large volumes. His life as a catholic priest and as a member of the University of Louvain has been focus, many times against the tide, on looking for the essence of human beings. Human beings are mainly religious beings for Ries. He doesn’t show religious experience in a unilateral and apologetic way but from an interdisciplinary which includes history of religious, general history, culture, sociology and paleoanthropology. For the Christian religion, religious experience leads human beings from dignity of the human person to God itself, in this case through the Mystery of the Light which is due to the person of Christ.
Keywords: Julien Ries; M. Eliade; religious experience; history of religious; homo religiosus; transcendence